Explaining the visual attention model in impulsive purchase behavior of tourism industry customers by theme analysis method - Farokhi, Sajad; Namamian, Farshid; Asghari Sarem, Ali; Ghobadi Lamuki, Tohfe (Journal of Islamic marketing, 2024)
Purpose This study aims to explain the model of impulsive purchase behavior in the Islamic Republic of Iran’s tourism industry. Design/methodology/approach This study uses the inductive–deductive approach for data collection. Field (interviews) and library (articles, books and theses) methods have been used for data collection. After determining the research variables, content analysis units (theme, category and markers) are specified. Academic experts and professionals in the subject area helped during the model design stage. Findings The results reveal 14 visual attention variables which are classified into four categories: attractiveness in the market, emotional reactions, improving the shopping style of tourists and visual advertising. Research limitations/implications This study focuses only on Iran. There is scope to expand the discussion with more interviews. The impact of the COVID-19 pandemic on tourism presented some unique challenges in participant recruitment. Future studies could focus on other Middle Eastern countries or other international areas. Moreover, future researchers could analyze other variables affecting impulsive purchase. Originality/value No other studies on tourism industry marketing have recognized the effective variables in impulsive purchase. To fill this gap, this paper explains the visual attention model in tourists’ impulsive purchase behavior.